Nonresearch Pharmaceutical Industry Payments to Oncology Physician Editors. (20th April 2020) - Haque, Waqas; Alvarenga, Maria; Hsiehchen, David
Abstract: Journal editors are gatekeepers of knowledge, and pharmaceutical industry payments to oncology editors have not been previously characterized. We performed a cross‐sectional study of nonresearch industry payments to editors of 26 oncology research journals. A total of 433 editors were eligible for inclusion in the CMS Open Payments database from 2013 to 2018. A total of 80% of eligible editors had nonresearch payments, and the mean value of payments per editor was $106, 778, which has increased over time. Only 5 out of 26 journals disclosed editor conflicts of interest and 3 of these journals reported at least one editor with no nonresearch industry payments but were found to have nonresearch payments. There was a positive correlation between journal impact factor and the average payment per editor for each journal. Our study shows the high prevalence and lack of transparency of nonresearch industry payments to oncology editors. Higher impact journals appear to be associated with greater nonresearch industry payments. Abstract : Pharmaceutical industry payments to physicians can potentially affect decision‐making and prescribing behaviors. This article reports potential conflicts of interest related to non‐research pharmaceutical payments to oncology editors and calls for greater transparency.